Impact of Ageing and Generational Effects on Household Energy Consumption Behavior: Evidence from Pakistan - Misbah Aslam; Eatzaz Ahmad (Energies, 2018)
Demographic shift is a worldwide phenomenon, which is mainly common among industrialized nations. However, in the age of fast technology transfer and globalization policy makers cannot undervalue population aging in developing countries, like Pakistan. The relationship between population aging, combined with joint family system, and energy demand has gained importance in Pakistan during the recent times. On the basis of a detailed analysis of micro data spanning over period of 16 years, this study explores the role of generational behavior towards energy consumption, while considering the effects of cohort and age, along with other determinants of energy demand. The decomposition of energy consumption exhibits significant differences in cohort and age effects. The study concludes that, in addition to aging effects, policy makers cannot ignore the recent generation’s trends of spending increasingly more on energy than previous generations.